Anti-mitotic Activities of Ethanolic Extract and Glutinol from Uvaria rufa Blume - Alimboyoguen, Agnes B.; De Castro-Cruz, Kathlia A.; Shen, Chien-Chang; Tsai, Po-Wei (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: This study describes the isolation of major chemical constituent from the bark of Uvaria rufa Blume, commonly known as “allagat or susong kalabaw”, an indigenous Philippine medicinal plant that belongs to the family Annonaceae. It is a short climbing shrub that grows in low and medium-altitude forests in the country. Materials and Methods: The bark samples of U. rufa were air-dried for three months without exposure to sunlight. The samples were ground in a blender, then, soaked in CH₂Cl₂ and in ethanol for three days and then, filtered. The crude extract of U. rufa was chromatographed on a gravity column dry packed with silica gel and was fractionated by silica gel chromatography using increasing proportion of acetone in CH₂Cl₂ at 10% increment. The purified isolates were subjected to NMR for structure elucidation. Their structures were identified mainly by using ¹H-NMR and by comparing current NMR data with those reported in the literature. Results: The results showed that the air-dried bark dichloromethane extract of the plant afforded glutinol. Glutinol and ethanolic extract exhibited anti-mitotic activity (18.33 % and 18.93 %, respectively), comparable to methotrexate (19.07 %), a well-known anti-cancer drug and even more potent in which they surpassed by 0.74 % and 0.14 %. Conclusion: The dichloromethane extract of the bark of U. rufa afforded glutinol that can be one the main metabolites responsible for the anti-mitotic activity of the plant. It may also contained other substances that might have great potential as novel therapeutic agents for cancer.
Keywords: Uvaria rufa; Allagat; Glutinol; Anti-mitotic; Triterpene